Pengaruh Pembelajaran Team Teaching Berbasis Integrasi Ilmu terhadap Motivasi Belajar dan Prestasi Belajar Siswa Madrasah Tsanawiyah Ummusshabri Kendari - Supriyanto, Supriyanto; Fathorrohman, Fathorrohman; Rachmawati, Ike Kusdyah (Shautut Tarbiyah-IAIN Kendari, 2025)
This research is based on the importance of cross-disciplinary teacher collaboration in creating meaningful learning processes and increasing student engagement and academic achievement. The integrated team teaching model is believed to not only have a direct impact on student learning outcomes, but also shape psychological aspects such as motivation, which in turn contributes to academic achievement. This study aimed to determine and analyze the effect of integrated science-based team teaching on student learning motivation and achievement, as well as to examine the mediating role of learning motivation in the relationship between learning and achievement. This study was conducted on 174 eighth-grade students at MTs Ummusshabri Kendari. Data were collected using a questionnaire distributed to the students. The collected data were tabulated and analyzed using descriptive and statistical analyses with path analysis. The results of this study indicate that team teaching learning based on science integration has a positive and significant effect on students' learning motivation; team teaching learning based on science integration also has a positive and significant effect on students' learning achievement; learning motivation has a positive and significant effect on students' learning achievement; and learning motivation partially mediates the effect of team teaching learning based on science integration on students' learning achievement. Another important finding is that team teaching had the most dominant influence on learning motivation. The implications of this study emphasize the importance of implementing a cross-disciplinary collaborative learning model that not only enriches the learning process but also strengthens students' motivational drive as a basis for improving academic achievement.